2014
DOI: 10.1007/s10753-014-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Melanocortin Peptides: Potential Targets in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease resulting in loss of self-tolerance with multiple organs, such as the kidney, skin, joints, and the central nervous system (CNS), being targeted. Numerous immunosuppressant therapies are currently being used for the treatment of SLE, but their clinical utility is somewhat variable because of the clinical heterogeneity. Melanocortins are a family of peptides derived from the common precursor protein pro-opiomelanocortin. These multifunctional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 97 publications
(117 reference statements)
0
29
0
Order By: Relevance
“…Leptin-induced activation of ObRb located on the POMC-neurons leads to an increase in the production of POMC-derived melanocortin peptides, primarily α-melanocyte-stimulating hormone (α-MSH), an agonist of types 3 and 4 melanocortin receptors (MC 3 R and MC 4 R) [51]. The α-MSH binds to MC 3/4 R located on GnRH-neurons, and stimulates the GnRH secretion by them.…”
Section: Hypothalamusmentioning
confidence: 99%
“…Leptin-induced activation of ObRb located on the POMC-neurons leads to an increase in the production of POMC-derived melanocortin peptides, primarily α-melanocyte-stimulating hormone (α-MSH), an agonist of types 3 and 4 melanocortin receptors (MC 3 R and MC 4 R) [51]. The α-MSH binds to MC 3/4 R located on GnRH-neurons, and stimulates the GnRH secretion by them.…”
Section: Hypothalamusmentioning
confidence: 99%
“…Several types of naturally occurring or synthetic oligopeptides and peptides have been reported to show immunomodulatory and anti-inflammatory activities [1][2][3][4] . Clinically used immunosuppressive drug cyclosporine has a cyclic peptide structure 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Immunomodulatory and anti-inflammatory activities of several types of naturally occurring or synthetic oligopeptides and peptides have been reported [1][2][3][4] . We have also found that certain types of peptide antibiotics suppress proliferation and several cytokine productions in mitogen-activated human peripheral blood mononuclear cells (PBMCs) 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…43 Increased anti-inflammatory and reduced pro-inflammatory cytokines by melanocortin peptides may be mediated by MC3R. 45 ACTH is the only known ligand for MC2R, which is highly expressed in adrenal cortex. 46 How these MCRs relate to clinical effects in OMS is unknown, because corticosteroids also exert significant effects on inflammatory mediators CXCL13 and BAFF in CSF and CCL21 and CCL22 in serum.…”
Section: Ae 2aementioning
confidence: 99%